Slack K(Na) channels influence dorsal horn synapses and nociceptive behavior - Evely, Katherine M (Mol Pain, 2017)
The sodium-activated potassium channel Slack (Kcnt1, Slo2.2) is highly expressed in dorsal root ganglion neurons where it regulates neuronal firing. Several studies have implicated the Slack channel in pain processing, but the precise mechanism or the levels within the sensory pathway where channels are involved remain unclear. Here, we furthered the behavioral characterization of Slack channel knockout mice and for the first time examined the role of Slack channels in the superficial, pain-processing lamina of the dorsal horn. We performed whole-cell recordings from spinal cord slices to examine the intrinsic and synaptic properties of putative inhibitory and excitatory lamina II interneurons. Slack channel deletion altered intrinsic properties and synaptic drive to favor an overall enhanced excitatory tone. We measured the amplitudes and paired pulse ratio of paired excitatory post-synaptic currents at primary afferent synapses evoked by electrical stimulation of the dorsal root entry zone. We found a substantial decrease in the paired pulse ratio at synapses in Slack deleted neurons compared to wildtype, indicating increased presynaptic release from primary afferents. Corroborating these data, plantar test showed Slack knockout mice have an enhanced nociceptive responsiveness to localized thermal stimuli compared to wildtype mice. Our findings suggest that Slack channels regulate synaptic transmission within the spinal cord dorsal horn and by doing so establishes the threshold for thermal nociception.